Theoretical and Methodological Trends in Public Sector Accounting Research (2017–2022): A Structured Literature Review of Six International Journals - Nashirotun Nisa Nurharjanti (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2025)
This study maps the trend of using theory and methodological approaches in public sector accounting research between 2017 and 2022. This research was conducted with a journal-bound sampling design from six international journals that consistently publish public sector accounting research. The total number of articles tabulated during the observation period was 975 articles. For the theory mapping, articles were screened based on the criteria of